Two Infinite Sequences of Pre-Maximal Extensions of the Relevant Logic E - Typańska-Czajka, Lidia (Bulletin of the Section of Logic, 2019)
The only maximal extension of the logic of relevant entailment E is the classical logic CL. A logic L ⊆ [E,CL] called pre-maximal if and only if L is a coatom in the interval [E,CL]. We present two denumerable infinite sequences of premaximal extensions of the logic E. Note that for the relevant logic R there exist exactly three pre-maximal logics, i.e. coatoms in the interval [R,CL].